Complicaciones obstétricas en multigestas adolescentes. Hospital Nacional Dos de Mayo 2009-2013. - Aparicio Ponce, Jorge Renato (2019)
Objective: To determine the obstetric complications in multigravid adolescent. Methods: Case-control study conducted at the National Hospital Dos de Mayo from 2009 to 2013. A documentary analysis of the clinical histories of 1,383 pregnant adolescents was carried out. The chi square test was used. For the statistically significant variables, a multinomial logistic regression was performed. Results: 1,383 clinical histories of pregnant adolescents were admitted; 342 were multigravid adolescents. There were 334 cases of morbidity, the most frequent being anemia (50.3%), vaginal infection (18.7%) and premature rupture of membranes (11.4%). There was only a statistically significant association between multigravida adolescent and pregnancy-induced hypertension (p 0.032) (OR = 0.54 IC 95% [0.31-0.96]). Conclusions: The condition of multigravida adolescent protects in 46% of cases to suffer from hypertension induced by pregnancy. There is no difference from other morbidities between primigravid and multigravida adolescent.